DEVELOPMENT OF TOURISM IN UZBEKISTAN (1991-2023) - Doston Oblokulov O‘Ktamovich Bukhdu (American Journals, 2023)
This article discusses the stages of tourism development in Uzbekistan. It is mentioned that tourism is a developed sector.
Keywords: tourism, historical and cultural monuments, infrastructure, state, modernization.